P.010 The Canadian Neurosurgery Research Collaborative (CNRC): A novel, trainee-led, nationwide multicentre research network. (17th June 2016) - Dakson, A; Bigder, M; Elliott, C; Guha, D; Iorio-Morin, C; Kameda-Smith, M; Lavergne, P; Makarenko, S; Taccone, MS; Tso, M; Wang, B; Winkler-Schwartz, A; et al.
Abstract : Background: The goals of evidence-based neurosurgery are to improve surgical outcomes, reduce complications, and provide an objective basis for altering practice. The need for higher quality studies, typically prospective and multicentre, has been growing especially in light of the evolving complexity of neurosurgical interventions and heterogeneity of patient populations. In the United Kingdom (UK), trainee-led research collaboratives have been established to tackle this problem. Therefore, we sought to evaluate the potential role for a resident-led research collaborative in neurosurgery in Canada based on the UK experience. Methods: A literature review of trainee-led collaboratives was conducted utilizing PubMed and Medline. Identified articles were reviewed for study quality and clinical relevance to explore the potential benefits of collaboratives. Results: In the UK, 27 collaboratives have been established in various specialties by trainees. Some published high quality trials with implications on their clinical fields. Evidence suggests that such endeavors improves trainees' research skills and may help cultivate a research culture tailored towards clinical trials. Conclusions: Given the growing evidence for research collaboratives in the UK, we propose launching the Canadian Neurosurgery Research Collaborative (CNRC) which currently represents 12 out of 14 neurosurgery programs in Canada, and planning its first multicenter prospective study.